Apparatisation in & of Architecture - Sang Lee; Henriette Bier (Spool, 2019)
Apparatus and apparatisation, the focus of the Cyber-Physical Architecture (CpA) issue #2 of SPOOL, refer to an assemblage of various components, tools, and instruments that in combination produce an exponential surplus beyond the linear sum of parts. On the one hand, apparatus can be seen as a collective of means used to perform certain tasks in order to solve a range of problems. It can contain a series of tools and instruments and produce new rationalities that often translate into pervasive technology, such as, for instance, electricity and, today, Information and Communication Technology (ICT). On the other hand, apparatuses can be found in organisations and institutions that deal with various aspects of a society. For example, the police apparatus, of which rationalities are – rather than being embodied in physical technics – codified in written statutes. The apparatus in this sense is a collection of performative concepts that the subjective members of the apparatus execute in order to serve policies and plans.